Victory on Earth or in Heaven : Mexico's Religionero Rebellion - Stauffer, Brian A. (Book collections on Project MUSE., 2019)
This work reconstructs the history of Mexico's forgotten ""Religionero"" rebellion of 1873-1877, an armed Catholic challenge to the government of Sebastián Lerdo de Tejada.